Urban green spaces as a component of an ecosystem. Functions, services, users, community involvement, initiatives and actions - Vargas-Hernández, José G.; Pallagst, Karina; Zdunek-Wielgolaska, Justyna (Revista de Urbanismo, 2017)
This paper aims to the review the existing literature on some important features of urban green spaces such as the components, functions, services, community involvement, initiatives and actions from an ecosystem perspective. The analysis begins from the assumption that urban green spaces are ecosystems of vital importance in enhancing the quality of life in an urban environment and supplying ecosystem services such as biodiversity and climate regulation. Thus, the urban green space is an important component of an ecosystem in any community development. Meeting the needs of users is related with the functions and services that urban green spaces provide to communities. Community involvement, engagement and development require mechanisms to ensure meeting the needs and aspirations of local users in the community. The methods employed in this analysis are the literature and documents review, and analysis of existing data on uses and users. As conclusions, the paper suggests environmental, economic and social initiatives for local authorities and communities that can be applied to all represented and involved stakeholders.